Assessment of Water Quality Index Parameters During Raining and Dry Season Flow on River Sg. Batang Labu and Sg. Semenyih - Chooi, Bryan Kou Sing (2018)
River Water Quality assessment has been a key importance for the community and authority on how to sustain the local river quality. The main aim of the research is to determine the WQI using the six major parameters of DO, BOD, COD, AN, TSS and pH during different seasonal changes at industrial (Sg Semenyih) and rural area (Sg. Batang Labu). Samples were collected six times in total with the sum up amount of 72 data. Parameters such as the DO and pH are conducted in-situ, where as the other four parameters were tested in laboratory. This study was found out the degree of pollution during dry season is higher than wet season. On the other hand, the degree of pollution of Industrial Area are higher than Rural Area. Base on the DOE-WQI for the two rivers are classified under the category “Clean”. Whereas during the dry season it was found out that Semenyih river which influenced by industrial were classified under the category “Slightly Polluted”. As per in WQI, both rivers classified under Class II. Despite both rivers have the similar classifications, but issues and problems affecting these rivers are different. For Semenyih river that exposed to the industrial and surface runoff from the nearby town were the main factors causing near to Class III with a WQI of 80.95 during dry season. Whereas the Batang Labu river coming from rural area was mostly affected by the anthropogenic and agriculture activities hence leading to a safe Class II classification with a WQI of 91.05 during the wet season, but if a better effort or slight treatment from the local community to the river, Class I classification will be at ease (WQI >92.7). This research is vital to know the current water quality of river for the local authority and community.